2014
DOI: 10.1364/ol.39.006466
|View full text |Cite
|
Sign up to set email alerts
|

Single-shot phase imaging with a coded aperture

Abstract: We present a method of quantitatively acquiring a large complex field, containing not only amplitude information but also phase information, based on single-shot phase imaging with a coded aperture (SPICA). In SPICA, the propagating field from an object illuminated by partially coherent visible light is sieved by a coded mask, and the sieved field propagates to an image sensor, where it is captured. The sieved field is recovered from the single captured intensity image via a phase retrieval algorithm with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(45 citation statements)
references
References 20 publications
0
45
0
Order By: Relevance
“…Phase is recovered based on multiple images with some type of data diversity that translates phase information into intensity (e.g. defocus [5], illumination coding [31], pupil coding [32]). Here we adopt a pupil-coding scheme where the wavefront at the exit pupil [12] is differently aberrated for each measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Phase is recovered based on multiple images with some type of data diversity that translates phase information into intensity (e.g. defocus [5], illumination coding [31], pupil coding [32]). Here we adopt a pupil-coding scheme where the wavefront at the exit pupil [12] is differently aberrated for each measurement.…”
Section: Methodsmentioning
confidence: 99%
“…A CA has been used to improve the reconstruction conditions because its Fourier spectrum is significantly extended compared with that of a conventional non-coded aperture. Using CAs, single-shot amplitude imaging with incoherent light and single-shot reference-free DH with coherent light have been demonstrated [18][19][20][21][22][23].…”
Section: 2 Methodsmentioning
confidence: 99%
“…Focusing is required to generate the diverging illumination for high magnification and resolution. Note that also for parallel beam propagation imaging it is extremely common to implicitly assume perfect plane wave illumination by performing the conventional flat-field correction [3,[7][8][9][10][11]. In previous studies, we have shown that under these conditions the commonly used standard flat-field correction, i.e.…”
Section: Introductionmentioning
confidence: 99%